Impact Evaluation of Investments in the Appalachian Region: A Reappraisal. (November 2018) - Sayago-Gomez, Juan-Tomás; Piras, Gianfranco; Jackson, Randall; Lacombe, Donald
We evaluate the impact of a half century of nontransportation Appalachian Regional Commission (ARC) investments on its constituent counties using quasi-experimental methods. We apply a set of propensity score methods and select the most appropriate matching algorithm for use in identifying the effects of policy implementation. The results of the analyses indicate that counties that received ARC funding grew faster than the control counties. The long-run per capita income growth rate in ARC investment counties was an average of 5.5 percent higher than in the control counties. Employment also grew significantly faster in these ARC counties than in the control counties for most of the study period. The average difference in the long-run employment growth rates between the counties that received ARC investments and those counties that did not was approximately 4.2 percent.